A course in domestic sciences for the first year in night school - Grizzell, Gertrude (My University, 1908)
Introduction: Manual training originated in Europe several years ago. At first it was used as a means of developing industrial skill. Later, manual training was introduced into this country by certain broad minded men, who foresaw the advantage of such training. The European system has been modified and adapted to the needs of the American school, and educators feel that it is fulfilling the want that has become a permanent part of our school system.
Citation: Grizzell, Gertrude. A course in domestic sciences for the first year in night school. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Domestic Science; Home Economics; Education; Graduating theses; Senior theses; Theses